Preparation parameter optimization method for preparing polymer film by spin-coating method

By analyzing the physical attribute correlation of the prefabricated solution of the polymer, optimizing the rotary paint parameters, solving the problem of inaccurate control of polymer film in the existing technology, and achieved precise pre -setting of high -efficiency rotary coating process control and thin film thickness.

CN119368401APending Publication Date: 2025-01-28BEIJING UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411407774.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively set the preformed solution density and viscosity of polymer films based on the molecular weight and solvent density of polymer solutes, resulting in insufficient control of the accuracy of film thickness in the spin coating process.

Method used

By analyzing the correlation between the soluble molecular weight, solvent density and solution concentration and viscosity of the concentration and viscosity of the solvent, use the Mark-Houwink equation and the Huggins equation to determine the characteristics of the characteristic viscosity and concentration of the polymer solution, and then optimize the rotary coating parameters to achieve the thin film Precision control of thickness.

Benefits of technology

The efficient control rotation coating process and rotary coating parameters based on the basic physical properties of polymer thin film components are implemented, and the pre -set accuracy and prepaid efficiency of the thickness of the polymer thin film will be improved, and the discreteness and deviation of the thin film thickness will be reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368401A_ABST
    Figure CN119368401A_ABST
Patent Text Reader

Abstract

The invention provides a preparation parameter optimization method for preparing a polymer film by a spin-coating method. The method comprises the following steps: firstly, prefabricating a film sample and analyzing the correlation between the film thickness and polymer component physical properties and spin-coating parameters to obtain three parameters, namely a dissipation coefficient caused by a spin-coating process, the dispersion of the film thickness of the sample caused by an experimental environment and the deviation degree between the film thickness and an expected thickness; and analyzing and obtaining the optimal spin-coating time and spin-coating speed in the film preparation process according to the thickness value of the polymer film to be prepared and based on the three parameters. The spin-coating process is efficiently controlled and the spin-coating parameters are effectively set on the basis of basic physical attributes of polymer film components and film thickness information.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention is applied to the technical field of preparing polymer films by spin coating. Firstly, by prefabricating a film sample and analyzing the relationship between the film thickness and the physical properties of the polymer component and the spin coating parameters, three parameters are obtained, namely, the dissipation coefficient caused by the spin coating process, the discreteness of the sample film thickness caused by the experimental environment, and the deviation between the sample thickness and the expected thickness; then, for the thickness value of the polymer film to be prepared, based on the above three parameters, the optimal spin coating time and spin coating speed in the film preparation process are analyzed and obtained. Based on the basic physical properties of the polymer film components and the film thickness information, the spin coating process can be efficiently controlled and the spin coating parameters can be effectively set. Background Art

[0002] Due to its superior mechanical flexibility and dielectric breakdown strength, polymer materials have broad application prospects in micro-nanoscale electronic devices. Spin coating is one of the commonly used technical methods in the field of material research and electronic device preparation due to its easy control of preparation process and easy regulation of mechanical properties of thin film specimens. It is preferred by researchers and engineering technicians.

[0003] The precise setting of spin coating parameters is the key technology for the efficient preparation of polymer films by spin coating. Ignoring the influence of fluid volatilization during the preparation process, Emslie et al. equated the viscosity change during spin coating to the change of rotation speed, theoretically analyzed the correlation between solution viscosity and rotation speed during spin coating, and pointed out that the change rate of film thickness during spin coating increases with the increase of film thickness. Meyerhofer et al. further considered the influence of solvent volatilization during spin coating, obtained the variation law of film thickness with the viscosity of prefabricated solution, spin coating speed and volatility, and pointed out that the film thickness during spin coating increases with the increase of prefabricated solution viscosity. Subsequently, Chapman et al. considered the inhomogeneity of prefabricated solution concentration and viscosity, constructed a correlation model between the thickness and the density, viscosity and volatility of prefabricated solution when preparing polymer films by spin coating, and pointed out that the film thickness is inversely proportional to the square root of the spin coating speed. Hall et al. analyzed the homogenization process of prefabricated solution density, and pointed out that the film thickness increases with the increase of the initial viscosity of the prefabricated solution, but decreases with the increase of the initial solution density, spin coating speed and solution mass ratio.

[0004] It is worth noting that the physical properties of the polymer prefabricated solution mainly depend on the basic physical properties of the component solutes and solvents, such as solute molecular weight and solvent density. At present, in the research on thin film preparation technology, the effective setting of the density and viscosity of the thin film prefabricated solution based on the solute molecular weight and solvent density has not been achieved, and the accuracy control of the thickness of the polymer film prepared by the spin coating process needs to be improved. This technology is based on the correlation between the thickness of the sample film and the molecular weight of its component solutes, solvent density and spin coating parameters, and considers the influence of the spin coating process and experimental environment on the viscosity of the prefabricated solution and the film thickness. The dissipation coefficient, deviation from the expected thickness and film thickness dispersion parameters of the polymer film prepared by spin coating are analyzed. Then, through the minimization analysis of the latter two parameters, the optimal spin coating parameters for preparing thin films by spin coating are obtained, and the pre-setting of the polymer film thickness and the improvement of the preparation efficiency are achieved. Summary of the invention

[0005] The correlation between the solute molecular weight, solvent density, solution concentration and viscosity of the polymer preformed solution was analyzed, and a simplified analysis method for determining the viscosity of the preformed solution based on the basic physical properties of the polymer solution components (solute molecular weight, solvent initial density and viscosity) was implemented.

[0006] By testing and analyzing the sample film thickness dissipation coefficient, the deviation from the corresponding expected thickness and the film thickness dispersion, the thickness pre-control and spin coating parameter optimization can be achieved when the polymer film is prepared by spin coating.

[0007] The technical solution adopted by the present invention to solve the technical problem is as follows:

[0008] 1. Determine the correlation between the concentration and viscosity of the polymer preformed solution based on the volume and mass percentage of the polymer preformed solution, the molecular weight and density of the solute, and the density of the solvent.

[0009] (1) Determination of the intrinsic viscosity of the solution. According to the Mark-Houwink equation, the intrinsic viscosity of the polymer [η], that is, the relative viscosity of the polymer solution when the concentration approaches zero, can be expressed as

[0010] [η] = KM a (1.1) Where M is the molecular weight of the polymer solute, which can be measured by light scattering and osmotic pressure methods; K and a are the Mark-Houwink proportional constant and empirical parameter, respectively. The values ​​of K and a are affected by the ambient temperature, the properties of the solvent, and the size of the polymer molecular weight. During the test, first, by preparing polymer solutions of different concentrations, measuring the time required for the solvent and solution to flow through the specific scale of the viscometer, and calculating the time ratio (t0 / t), the relative viscosity η of the sample is obtained. r ; Then, according to the relative viscosity η of each group rThe test results were plotted and extrapolated to zero concentration to obtain the intrinsic viscosity [η] of the solution; further, lg[η]-lgM was plotted with the logarithm of the intrinsic viscosity of the sample lg[η] and the logarithm of the molecular weight lgM to obtain the proportionality constant K and the empirical parameter a (whose slope is a, and the intercept on the y-axis is lgK).

[0011] (2) Determine the concentration and viscosity of the solution based on the solution volume and mass percentage, solute molecular weight and density, solvent density and initial viscosity.

[0012] Solution density ρ is the mass percentage of solution W t , solute density ρ m and solvent density ρ s The function of For a solution with a single solute, the concentration c of the solution is determined by the mass percentage W of the solution. t and solution density ρ, namely

[0013] The viscosity of dilute polymer solutions is often described by the Huggins equation

[0014] η=η s [c·[η]+K H (c · [η]) 2 +B n (c · [η]) n +1](1.2)

[0015] Where η and c are the viscosity and concentration of the polymer solution, respectively. s is the initial viscosity of the solvent, K H The dimensionless numerical factor that characterizes the hydrodynamic and thermodynamic interactions of polymers in solution is called the Huggins coefficient. n , n are Huggins high-order coefficient and fractional index, respectively, which are related to the molecular weight of polymer solute and initial viscosity of solvent. Based on (1.2), the viscosity test and fitting analysis of solution samples with different concentrations can obtain the Huggins coefficient K of polymer solution: H and the higher-order parameter B n and fractional exponent n.

[0016] Combining (1.1) and (1.2), the viscosity η of the polymer solution, the concentration c, and the initial viscosity η of the solvent s , the relationship between the solute molecular weight M is expressed as:

[0017] η=η s (cKM a +K H c 2 K 2 M 2a +Bn c n K n M na +1)(1.3)

[0018] That is, based on the correlation coefficients K, a, and K of the polymer solute molecular weight and the initial viscosity of the solvent H , B n , n, the correlation between the viscosity η and concentration c of the polymer solution can be determined.

[0019] Furthermore, combining (1.3) we can obtain that the viscosity of the polymer solution η and the initial viscosity of the solvent η s , mass percentage W t , solution density ρ, and solute molecular weight M are expressed as:

[0020]

[0021] It is worth noting that based on the statistical analysis of the concentration of a large number of polymer solutions, the influence of the fractional power function term in expression (1.4) is much greater than the other three terms. That is, the solution viscosity is the fractional exponential power of the basic physical properties of the solute and solvent, which can be simplified as:

[0022]

[0023] Among them, Mark-Houwink proportionality constant K, Huggins high-order coefficient B n , solution ratio mass percentage W t Both are related to the molecular weight of the polymer solute M and the initial viscosity of the solvent η s , solution density ρ. The fractional index n is a positive fraction greater than 1. Therefore, for the intuitiveness of experimental techniques, the combined effect of the basic physical properties of solute and solvent on solution viscosity η can be expressed as C n :

[0024]

[0025] That is, the viscosity of the polymer solution can be approximately expressed as a power function of the mass percentage of the mixed solution and the density. n By measuring the viscosity η of each sample solution and the initial viscosity η of the solvent s , mass ratio percentage W t , solution volume V and polymer solute molecular weight M are measured and statistically obtained (C n =η s K n B n M na ), n is the Huggins fraction index.

[0026] 2. Determine the expected thickness of polymer films prepared by spin coating based on the basic physical properties of the solute and solvent.

[0027] The spin coating process of the thin film needs to consider the influence of two effects at the same time, namely the thinning effect of the thin film under ideal experimental conditions and the influence of factors such as ambient temperature, humidity, and solution volatilization on the film thickness under actual experimental conditions.

[0028] In view of the thinning effect of the film caused by the spin coating process, Emslie et al. theoretically analyzed the correlation between the spin coating parameters (rotation speed and spin coating time) and the physical properties of the solution (density and viscosity), and obtained the theoretical thickness h of the film during the preparation of the polymer film. s , spin coating speed ω, spin coating time t:

[0029]

[0030] Where h0 is the initial solution layer thickness, ρ is the density of the polymer solution, and η is the viscosity of the preformed solution.

[0031] As we all know, the volatilization of solution is inevitable during the spin coating process, which leads to an increase in solution viscosity and affects the flow and film formation process of the film. Therefore, under actual experimental conditions, experimental environmental factors and solution volatility need to be considered. In order to analyze the dissipation caused by solution volatility, the dissipation coefficient δ is introduced in this experimental technique to characterize the effect of experimental conditions on the thinning of the film thickness:

[0032] δ=h s / h t (1.8)

[0033] Among them, h t is the expected thickness of the film. Therefore, when the polymer film is prepared by spin coating, the expected thickness of the specimen can be expressed as:

[0034]

[0035] In order to ensure the accuracy of the experimental data and reduce the impact of experimental errors on the results, more than six groups of valid samples were prepared during the statistical analysis. t i and compared with the theoretical thickness to obtain the dissipation coefficient.

[0036] 3. Analyze the discreteness of the thickness of polymer film samples prepared by spin coating and its deviation from the expected thickness, and obtain the optimal spin coating parameters for spin coating preparation of polymer films.

[0037] Assume the spin coating parameter x = ω 2 t. Corresponding spin coating parameters of each group of samples during the experiment Preset values ​​for spin coating parameters The deviation is zi =x i / x0-1. From the analysis of formula (1.9), it can be seen that the expected thickness of the sample film (h r ) and the theoretical film thickness (h s ), preset spin coating parameters and spin coating parameter deviation (z i ). For a specific solute and solvent, the physical properties of the solute and solvent are determined, and the actual thickness of the sample film h t It can be expressed as:

[0038]

[0039] The coefficient of the first-order term and the quadratic coefficient The deviation α between the thickness of the film prepared by this technology and the expected thickness is characterized respectively dev And the dispersion α of each sample film div . Using α div and α dev At the same time, when the spin coating parameters are at the minimum value, the prepared film has a high degree of consistency with the expected thickness and the thickness dispersion of each sample is low.

[0040] In summary, in order to achieve effective preparation of spin-coated thin films, the thickness control and discreteness control of each thin film product can be achieved by optimizing the spin-coating parameters: first, the preliminary spin-coating parameters are set and the thin film is prefabricated, and the precise value of the dissipation coefficient δ is calculated based on the actual measured film thickness and the theoretical thickness value; then, the film thickness deviation α caused by the film preparation experimental environment is considered. dev and dispersion α div Influence, determine the target spin coating parameter ω 2 t. The entire test and optimization process is as follows Figure 1 shown.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] 1. In this experimental technique, considering the influence of the spin coating process, the dissipation coefficient δ is introduced to characterize the thinning phenomenon of the film thickness caused by the spin coating process. This technology helps to control the thickness of the film sample when the material is spin-coated.

[0043] 2. In this experimental technique, the influence of the experimental environment on the physical properties and thickness of the film is considered. The deviation α between the sample film thickness and the expected thickness is dev and thickness dispersion α div Through testing and analysis, the optimal spin coating parameters can be obtained, and precise control of film thickness can be achieved during batch preparation of polymer films.

[0044] 3. The method provided by this experimental technology not only has significant effects in laboratory-scale research, but also has wide applicability in industrial production. Whether it is small-scale trial production or large-scale industrial production, by reasonably configuring the film prefabricated solution and setting the spin coating parameters, the thickness and physical property discreteness of the polymer film specimen can be reduced, making this method have broad application prospects in various fields, such as electronic devices, thin film sensors, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 Schematic diagram of the spin coating parameter setting process for preparing thin films by spin coating

[0046] Figure 2 lg[η]-lgM fitting diagram of PVDF film sample

[0047] Figure 3 Schematic diagram of the correlation between the concentration c and viscosity η of PVDF / DMF preformed solution

[0048] Figure 4 Dissipation coefficient of the first group of PVDF / DMF film samples

[0049] Figure 5 Schematic diagram of the thickness discreteness of the second group of PVDF / DMF film samples DETAILED DESCRIPTION

[0050] The present technology provides a method for optimizing spin coating parameters for preparing polymer films based on spin coating. This method aims to achieve viscosity control of polymer film prefabricated solution and optimization of spin coating parameters. The following two examples provide the determination of three parameters: dissipation coefficient, thickness dispersion, and deviation from expected thickness when preparing polyvinylidene fluoride / N,N-dimethylformamide (PVDF / DMF) polymer films by spin coating, and the process of optimizing the setting of spin coating parameters when preparing films of expected thickness.

[0051] Example 1: The correlation between the concentration c and viscosity η of the polymer preformed solution is obtained by preparing a PVDF / DMF polymer film and measuring its thickness.

[0052] Step (1): The density and initial viscosity are 944 kg / m 3 and 8.02×10 -4 Pa·s N,N-dimethylformamide (DMF) is used as solvent, and the molecular weight and density are 400 kg / mol and 1780 kg / m 3 PVDF powder is used as the solute, and a solution with a mass fraction of 15% is prepared. The area of ​​the substrate is 10 -4 m 2 The volume and density of the pre-made solution used in the preparation of PVDF / DMF polymer film were 9×10 -8 m3 and 1015.54 kg·m -3 .

[0053] Lutringer and Weill and Ayad, Carrot applied light scattering and glass capillary viscosity test methods to analyze the PVDF solute molecular weight and solution intrinsic viscosity of PVDF / DMF polymer solution (Lutringer, G., Weill, G., Polymer, 1991, 32 (5), 877-883) (Ayad, D., et al., Int. J. Polym. Anal. Charact., 2001, 6 (6), 619-637), as shown in Table 1. Based on (1.1), the solute molecular weight and solution intrinsic viscosity were fitted and analyzed, as shown in Table 1. Figure 2 As shown in the figure, the Mark-Houwink proportional constant K and empirical parameter a can be obtained, which are K = 1.95 × 10 -2 cm 3 ·mol 0.73 g -1.73 =3.02×10 -3 m 3 ·mol 0.73 kg -1.73 , a=0.73.

[0054] Table 1 Statistics of intrinsic viscosity and molecular weight of samples in the experiment

[0055]

[0056] Step (2): Based on the report by Xu and Ju that PVDF / DMF solution was prepared by spin coating and the viscosity of the solution was tested (Xu, L., et al., Polymers, 2023, 15(5), 1119), the Levenberg-Marquardt (LM) algorithm was used to calculate the solution concentration c and viscosity η (where M = 1100 kg / mol, W = 1100 kg / mol) of each group of solutions. t =10%, W t =12% ​​and W t =14% solution viscosity is 38.71Pa·s, 90.62Pa·s and 164.60Pa·s) and the correlation between concentration and viscosity of PVDF / DMF solution is obtained by nonlinear fitting. Figure 3 shown.

[0057] Based on (1.2), Figure 3 The nonlinear relationship between solution viscosity and concentration was further fitted to obtain the Huggins parameter K of PVDF / DMF solution. H , high-order parameters B n, the fractional index n are

[0058] K H =0.4, B n =5.24×10 -3 , n = 4.104

[0059] Therefore, the comprehensive influence coefficient C of PVDF / DMF solution in this experiment is n and viscosity η are

[0060] C n =η s K n B n M na =0.802×0.00302 4.104 ×5.24×400 4.104×0.73 ×10 -6 =1.194×10 - 8 Pa·s·m 12.312 kg -4.104

[0061] η=0.0293Pa·s+0.4274Pa·s+10.8435Pa·s+8.02×10 -4 Pa·s=11.3010Pa·s

[0062] It is worth noting that by analyzing the ratio of the terms on the right side of the above formula to the η value, it can be seen that the first term (c·η s The influence weight of the second term (K H ·η s ·(c·[η]) 2 ) weight is 3.7820%, and the high-order index term (B n ·η s ·(c·[η]) n ) weight is 95.9517%, the initial viscosity of the solvent η s The weight is 0.0071%. It can be seen that the solution viscosity is mainly affected by the fractional power function term B n ·η s ·(c·[η]) n This is consistent with the assumption (1.5) used in this experiment. The viscosity of the prefabricated solution in this experiment can be η=10.8435Pa·s.

[0063] Step (3): In this experiment, a vacuum spin coater and a two-stage spin coating technique were used to prepare a polyvinylidene fluoride film, wherein the low speed was set to 1000 RPM for 20 seconds and the high speed was set to 4000 RPM for 40 seconds.

[0064] Since the spin coating parameter analyzed in this experiment is ω 2 t, the above-mentioned secondary spin coating speed and time parameters (ω1=104.72rad / s, t1=20s; ω2=418.88rad / s, t2=40s) are equivalently converted into the equivalent uniform spin coating process speed ω0 and time t0 with high speed ω2 as reference:

[0065]

[0066] The equivalent spin coating speed ω0 and spin coating time t0 obtained in this experiment are

[0067] ω0=418.88rad / s,t0=55.3536s

[0068] And this spin coating parameter is used as the preset value of the spin coating parameter of the subsequent thin film specimen.

[0069] Step (4): Test the sample film thickness, analyze the correlation between the film thickness and the physical properties of the solute and solvent, and the spin coating parameters, and obtain the dissipation coefficient δ of the film spin coating process.

[0070] Substituting the physical properties of the solution in the experiment into equation (1.7), we can obtain the theoretical thickness of the film h under ideal experimental conditions and when the solution is a non-volatile fluid. s It is 28.7μm.

[0071] During the experimental operation, the dissipation coefficient δ of each sample i Characterized by the theoretical thickness of the film h s Expected thickness Ratio The PVDF polymer film prepared by the experimental parameters was statistically analyzed. Figure 4 As shown in Table 2. It can be seen that after removing the data points with large experimental errors, the data of seven samples are valid data. For the polymer solution with this ratio, the dissipation coefficient δ of the film prepared by spin coating is approximately 7.16.

[0072] Step (5): Combine the film thickness h of each group of samples ir , dissipation coefficient δ i , the deviation of the spin-coated polymer film from the expected thickness is obtained by analysis dev and thickness dispersion α div .

[0073] The spin coating parameters (ω 2 t) and the preset values ​​of spin coating parameters Deviation As shown in Table 2.

[0074] Table 2 Statistics of thickness, dissipation coefficient and spin coating parameter deviation of the first group of PVDF / DMF film samples

[0075]

[0076]

[0077] The sample data in this embodiment are analyzed to obtain the deviation degree α between the film sample and the expected thickness. dev and thickness dispersion α div In order to reduce instrument error and experimental operation error, three samples were randomly selected. Analyze for groups, and analyze and perform statistics on multiple groups of samples.

[0078] by Taking the data set as an example, the thickness and spin coating parameters of each sample are analyzed:

[0079]

[0080] Further calculation of the above formula yields

[0081]

[0082] Therefore, the linear and quadratic coefficients of the governing equation (1.10) are:

[0083]

[0084] Calculate the expected thickness deviation α of each sample group separately dev and thickness dispersion α div , and calculate its average value. We can get:

[0085]

[0086] When the expected thickness deviation α dev and thickness dispersion α div When both are minimum, the thickness of the sample film is closest to the expected thickness and the dispersion is minimum. Table 3 is the statistics of the five groups of sample data in the experiment. It can be seen that the data group The expected thickness deviation and thickness dispersion of α are both the smallest. dev =-1.4335×10 -5 m,α div =2.1290×10 -5 When m, the spin coating parameter deviation affects the thickness of the spin-coated film h t The impact can be expressed as:

[0087]

[0088] Table 3 Linear term coefficients and quadratic term coefficients for different data groups

[0089]

[0090] Example 2: The dissipation coefficient of the PVDF / DMF polymer film determined in Example 1 is prepared by spin coating, and the spin coating parameters are preset to achieve directional preparation of the polymer film.

[0091] Step (1): Prepare a PVDF / DMF pre-solution using the same solute and solvent as in Example 1, i.e., the solvent density of N,N-dimethylformamide (DMF) is 944 kg / m 3 , polyvinylidene fluoride (PVDF) powder is the solute, the molecular weight M and density are 400kg / mol and 1780kg / m 3 , mass fraction is 15%. The base area of ​​the film is 10 -4 m 2 Therefore, the proportional constant K and empirical parameter a of the film preparation process are the same as those in Example 1 (K = 3.02 × 10 -3 m 3 Lmol 0.73 kg -1.73 , a=0.73).

[0092] Step (2): Using the Huggins parameter K of the PVDF / DMF solution determined in Example 1 H , high-order parameters B n , fractional index n:

[0093] K H =0.4, B n =5.24×10 -3 , n = 4.104

[0094] The comprehensive influence coefficient and viscosity of the solution are

[0095] C n =η s K n B n M na =1.194×10 -8 Pa·s·m 12.312 kg -4.104

[0096]

[0097] Step (3): To prepare the target thickness h r = 8μm polyvinylidene fluoride film, the spin coating parameters are preset:

[0098] h s =δhr =5.728×10 -5 m

[0099]

[0100] In order to achieve precise control of the spin coating process, the rotation speed and time of the spin coater need to be set according to the target spin coating parameters, while considering the influence of the spin coating parameter deviation under specific conditions, and combining the deviation α of the expected thickness determined in Example 1 dev And the dispersion α of each sample film div , based on formula (2.1), the spin coating parameter deviation z is calculated to effectively control the spin coating parameter range. It can be obtained that the spin coating parameter deviation is

[0101] z I =1.3466,z II =0

[0102] where z Ⅰ =1.3466, the spin coating parameter deviation is much larger than the preset value and has no reference value. Therefore, the optimal value (z II =0). According to the determined spin coating parameter range, the spin coating parameters are optimized, and the setting accuracy of the spin coating instrument is considered (the spin coating speed accuracy is 100rpm, and the spin coating time accuracy is 1s), and the spin coating parameter deviation z=-0.0014 is determined. Under this deviation, the set spin coating parameters are closest to the target spin coating parameters, and the spin coating parameter deviation is the smallest, that is, ω0 2 t0=2427535rad 2 / s, ensuring the precise control of the thickness of the spin-coated film. The final spin-coating parameters are determined as low speed 800rpm, spin-coating time 51s; high speed 2000rpm, spin-coating time 21s. The speed and time of the spin-coating parameters are converted into the speed and time of the equivalent uniform spin-coating process, and the preset values ​​of the spin-coating parameters are:

[0103] ω0=209.44rad / s, t0=55.3409s

[0104] Step (4): Prepare thin film samples with determined spin coating parameters, and statistically analyze the film thickness, spin coating parameter deviation, and correlation of the spin coating parameters of each sample.

[0105] (i) The thickness of the experimentally prepared samples and the spin coating parameter deviations are shown in Table 4.

[0106] Table 4 Statistics of thickness and spin coating parameter deviation of the second group of PVDF film samples

[0107]

[0108] (ii) Compare and analyze the thickness of the thin film samples prepared based on the spin coating parameters determined by the control equation, and calculate the thickness of the thin film samples h it With target thickness h r = 8μm, and determine its discrete type

[0109]

[0110] The statistical results are shown in Table 5 and Figure 5 As shown:

[0111] Table 5 Thickness and discrete statistics of the second group of film samples

[0112]

[0113] From Table 5 and Figure 5 It can be seen that the thickness deviation of the polymer film determined based on the model and the thickness of the experimentally prepared sample is less than 2%. That is, under a specific environment, the dissipation coefficient δ is determined by prefabricating the film, and the spin coating parameters are adjusted based on the control equation taking into account the influence of the spin coating parameter deviation. The maximum discrete type of the expected thickness value and the measured thickness value does not exceed 2%. Compared with the simple model proposed by Bornside, Macosko and Scriven (prediction deviation is within 10%) in which Hall et al. experimentally measured the polymer film thickness, this method has a smaller prediction deviation and shows higher accuracy. Therefore, considering the influence of the spin coating process technology, the experimental environment and the volatilization of the solution, the relationship between the polymer film thickness h and the spin coating time ω and the spin coating speed t determined by this patent can be applied. The optimal spin coating speed and spin coating time are determined by prefabricating the film, so as to simplify the preparation process and improve the preparation efficiency.

[0114] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present application rather than to limit the technical solution of the present application. Any modification or equivalent substitution of the technical solution of the present application by ordinary technicians in this field should not deviate from the protection scope of the technical solution of the present application.

Claims

1. A method for optimizing the preparation parameters of a polymer film by spin coating, characterized in that: Determine the correlation between the concentration and viscosity of the polymer preformed solution based on the volume and mass percentage of the polymer preformed solution, the molecular weight and density of the solute, and the density of the solvent; (1) Determination of the intrinsic viscosity of the solution; According to the Mark-Houwink equation, the intrinsic viscosity of the polymer [η], that is, the specific viscosity of the polymer solution when the concentration approaches zero, is expressed as [η] = KM a (1.1) where M is the molecular weight of the polymer solute; K and a are the Mark-Houwink proportionality constant and empirical parameter, respectively; During the test, first, by preparing polymer solutions of different concentrations, measuring the time required for the solvent and solution to flow through the specific scale of the viscometer, and calculating the time ratio (t0 / t), the relative viscosity η of the sample was obtained. r ; Then, according to the relative viscosity η of each group r The test results are plotted and extrapolated to zero concentration to obtain the intrinsic viscosity [η] of the solution; further, lg[η]-lgM is plotted with the logarithm of the intrinsic viscosity of the sample lg[η] and the logarithm of the molecular weight lgM to obtain the proportional constant K and the empirical parameter a, whose slope is a and the intercept on the y-axis is lgK; (2) Determine the concentration and viscosity of the solution based on the solution volume and mass percentage, solute molecular weight and density, solvent density and initial viscosity; Solution density ρ is the mass percentage of solution W t , solute density ρ m and solvent density ρ s The function of For a solution with a single solute, the concentration c of the solution is determined by the mass percentage W of the solution. t and solution density ρ, namely The viscosity of dilute polymer solutions is described by the Huggins equation the=the s [c·[η]+K H (c·[η]) 2 +B n (c·[η]) n +1](1.2) Where η and c are the viscosity and concentration of the polymer solution, respectively. s is the initial viscosity of the solvent, K H The dimensionless numerical factor that characterizes the hydrodynamic and thermodynamic interactions of polymers in solution is called the Huggins coefficient; B n , n are Huggins high-order coefficient and fractional index, respectively, which are related to the molecular weight of polymer solute and initial viscosity of solvent. Based on the viscosity test and fitting analysis of solution samples with different concentrations, the Huggins coefficient K of polymer solution is obtained. H and the higher-order parameter B n and fractional exponent n; Combining (1.1) and (1.2), the viscosity η of the polymer solution, the concentration c, and the initial viscosity η of the solvent s , the relationship between the solute molecular weight M is expressed as: η=η s (cKM a +K H c 2 K 2 M 2a +B n c n K n M na +1)(1.3) That is, based on the correlation coefficients K, a, and K of the polymer solute molecular weight and the initial viscosity of the solvent H , B n , n, the correlation between the viscosity η and the concentration c of the polymer solution can be determined; Furthermore, the viscosity of the polymer solution η and the initial viscosity of the solvent η are combined to obtain s , mass percentage W t , solution density ρ, and solute molecular weight M are expressed as: η(W t ,p,M,h s )=η s (KW t pM a +K 2 W t 2 r 2 M 2a K H +K n W t n r n M na B n +1)(1.4) Based on the statistical analysis of the concentration of a large number of polymer solutions, the influence of the fractional power function term in the expression is far greater than the other three terms; that is, the solution viscosity is the fractional exponential power of the basic physical properties of the solute and solvent, which can be simplified as: η(W t ,p,M,h s )≈η s K n B n W t np n M na (1.5) Among them, Mark-Houwink proportionality constant K, Huggins high-order coefficient B n , solution ratio mass percentage W t Both are related to the molecular weight of the polymer solute M and the initial viscosity of the solvent η s , solution density ρ; the fractional exponent n is a positive fraction greater than 1. Therefore, for the intuitiveness of experimental techniques, the combined effect of the basic physical properties of solute and solvent on the solution viscosity η is expressed as C n : η(W t ,ρ,M,η s )≈C n W t n ρ n (1.6) That is, the viscosity of the polymer solution is approximately expressed as a power function of the mass percentage of the mixed solution and the density; among them, the comprehensive influence coefficient C n By measuring the viscosity η of each sample solution and the initial viscosity η of the solvent s , mass ratio percentage W t , solution volume V and polymer solute molecular weight M are measured and statistically obtained (C n =η s K n B n M na ), n is the Huggins score index; Determine the expected thickness of polymer films prepared by spin coating based on the basic physical properties of the solute and solvent; The spin coating process of the film needs to consider the influence of two effects at the same time, namely the film thinning effect under ideal experimental conditions and the influence of ambient temperature, humidity, and solution volatilization on the film thickness under actual experimental conditions; In view of the thinning effect of the film caused by the spin coating process, Emslie theory analyzes the correlation between the spin coating parameters and the physical properties of the solution, and obtains the theoretical thickness h of the film during the preparation of the polymer film. s , spin coating speed ω, spin coating time t: Where, h0 is the initial solution layer thickness, ρ is the polymer solution density, and η is the viscosity of the preformed solution; The dissipation coefficient δ is introduced to characterize the effect of experimental conditions on film thickness reduction: δ=h s / h t (1.8) Among them, h t is the expected thickness of the film; therefore, when the polymer film is prepared by spin coating, the expected thickness of the specimen is expressed as: Prepare more than six groups of valid samples; test the thickness of each sample The dissipation coefficient was obtained by comparing with the theoretical thickness; the discreteness of the thickness of the polymer film samples prepared by spin coating and its deviation from the expected thickness were analyzed to obtain the optimal spin coating parameters for the spin coating of the polymer film; Assume the spin coating parameter x = ω 2 t; Corresponding spin coating parameters of each group of samples during the experiment Preset values ​​for spin coating parameters The deviation is z i =x i / x0-1; the measured thickness of the sample film h t Expressed as: The coefficient of the first-order term and the quadratic coefficient Characterize the deviation of the film thickness prepared by this technology from the expected thickness α dev And the dispersion α of each sample film div .